Effect of mechanical activation on manganese extraction from manganese carbonate ore in acidic media - Yılmaz, Volkan Murat; Apaydin, Fatih; Yılmaz, Volkan Murat (Natl Inst Science Communication-Niscair, 2014)
A manganese carbonate ore has been mechanically activated at different milling times and the effect of mechanical activation on the ore structure is analyzed by X-ray diffraction, scanning electron microscopy and particle size analysis. The activation procedure leads to amorphisation and structural disordering of the ore structure. Sulfuric acid leaching of the non-activated and activated manganese carbonate ore has been studied at different temperatures, durations, and acid concentrations. The results show that dissolution of manganese increases from 69% to 100% in acidic leaching with 1 M H2SO4 at 70 degrees C after 30 min of mechanical activation, due to amorphisation in structure and creating more surface area.
Keywords: Acidic Leaching; Manganese Carbonate Ore; Manganese Extraction; Mechanical Activation